Isolation and characterization of LoAMS gene in anther development of lily (Lilium oriental hybrids). Issue 4 (1st October 2020) - Sui, Juanjuan; Cao, Xing; Yi, Mingfang; Wu, Jian; He, Junna
ABSTRACT: Lily is one of the most valuable fresh cut flowers in the world. However, pollen pollution brings inconvenience to retailers and consumers. Anther development is a complicated and precise process but much is unknown. In this study, the anther development key gene LoAMS was isolated from Lilium Oriental Hybrids cultivar 'Siberia'. Phylogenetic tree analysis and multiple sequence alignment showed that LoAMS protein had a typical basic helix–loop–helix domain (bHLH), belonging to the MYC transcription factor family. Furthermore, the subcellular localization experiment revealed that LoAMS was a nucleus protein. Transcriptional activation assays showed LoAMS was a transcriptional activator with the transcriptional activation domain in the last 204 amino acids (338-541aa) of the C-terminal region. The real-time quantitative PCR showed that LoAMS was abundant in lily anthers. Two peak expressions of LoAMS appeared in the anthers of 3-cm and 10-cm flower buds, especially in the microspores of 10-cm flower buds. These data indicate LoAMS is an anther specific transcriptional activator that may contribute to lily molecular breeding in the near future.